Porcine liver: experimental model for the intra-hepatic glissonian approach - Martins,Antonio Cavalcanti de Albuquerque (2008)
PURPOSE: The aim of the study is to evaluate the porcine liver as a teaching and training model for the glissonian approach. METHODS: Ten livers were removed from domestic adult white pigs weighting 35 to 45kg. Based on anatomical landmarks, the glissonian pedicles of each liver segments were dissected and biopsies were taken for histological examination, to analyze the presence of the glissonian sheath. RESULTS: During microscopic examination, a sheath of conjunctive tissue was observed wrapping each segmental pedicle in porcine liver. This could be clearly seen when histological preparation for connective tissue was obtained (Masson technique). CONCLUSION: The morphological arrangement of glissonian pedicles in porcine liver makes this model a useful tool for training the intra-hepatic glissonian approach.